2003
DOI: 10.1007/s11577-003-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Gewalt als Reaktion auf Anerkennungsdefizite?

Abstract: Zusammenfassung: Gewalt unter Jugendlichen geht überwiegend von männlichen Jugendlichen aus. Mit Daten des IKG-Jugendpanels aus dem Jahr 2001 mit türkischen, deutschen und Aussiedler-Jugendlichen, die die zehnte Jahrgangsstufe in Nordrhein-Westfalen besuchten, wird daher der Fokus auf die Erklärung des Gewalthandelns von 4.213 männlichen Jugendlichen gelegt. Dabei werden desintegrationstheoretische Überlegungen des Erklärungsansatzes von Wilhelm Heitmeyer und Reimund Anhut überprüft. Insbesondere weisen männli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Indeed, according to in this respect more reliable self-reported delinquency surveys, 6 the prevalence rates of violent as well as repeat offenders in the 1990s and 2000s were higher among youths from immigrant families than among juveniles of German origin. Most of these differences could be explained by social and educational disadvantage, a lack of social recognition (Babka von Gostomski, 2003; Bucerius, 2014) and a higher approval of violence-legitimizing norms of masculinity (Baier, 2015; Enzmann et al, 2004). Within the last 10 years one can observe that, in particular in the third generation of former labour migrants, these differences are getting smaller (Walburg, 2014).…”
Section: Prevalence and Development Of Crime And Delinquencymentioning
confidence: 99%
“…Indeed, according to in this respect more reliable self-reported delinquency surveys, 6 the prevalence rates of violent as well as repeat offenders in the 1990s and 2000s were higher among youths from immigrant families than among juveniles of German origin. Most of these differences could be explained by social and educational disadvantage, a lack of social recognition (Babka von Gostomski, 2003; Bucerius, 2014) and a higher approval of violence-legitimizing norms of masculinity (Baier, 2015; Enzmann et al, 2004). Within the last 10 years one can observe that, in particular in the third generation of former labour migrants, these differences are getting smaller (Walburg, 2014).…”
Section: Prevalence and Development Of Crime And Delinquencymentioning
confidence: 99%
“…They found that foreign children and youth are significantly more violent than other children and youth. Babka von Gostomski (2003) and Goldberg (2006) find that Turkish and ethnic German youth are involved in fighting much more often relative to Germans of non-migrant origin. Goldberg (2006) has examined the links between leisure activities such as computer games, sports, television and other media to explain differences in delinquent behaviour among youth with migration background and other youth.…”
Section: Youth and Deviant Behaviourmentioning
confidence: 99%
“…Schmitt-Rodermund and Silbereisen (2004), in their study among ethnic German youth with migration background, find a strong correlation between delinquency and the frequency of contact with other delinquent youth. Babka von Gostomski (2003) finds that the higher crime rates, especially among Turkish youth, are the result of socioeconomic disadvantage and lack of opportunities. investigated parentalpartner violence and found that Turkish youth reported three times more frequently that they had witnessed violent behaviour by their parents at home.…”
Section: Youth and Deviant Behaviourmentioning
confidence: 99%
“…Der Forschungsfrage der untersuchung lagen empirische Beobachtungen zugrunde, denen zufolge die Gewalttätigkeit Jugendlicher in missachtungserfahrungen in verschiedenen Sozialisationskontexten wurzeln kann (vgl. Helsper 1995;Allert 1997;Sutterlüty 2002;Babka von Gostomski 2003). Davon ausgehend wurde vermutet, dass verschiedene missachtungsweisen neben unterschiedlichen Verletzungsgraden spezifische Verletzungscharakteristika aufweisen können, die von den Betroffenen produktiv verarbeitet werden müssen.…”
Section: Das Konzept Der Anerkennungunclassified